Can enterprise digital transformation reduce carbon emissions? Evidence from listed industrial enterprises in China - Hu , Yu; Chen, Xiaofang; Chen, Xin; Wang, Zhitao (Transformations In Business & Economics, 2026)
Digital transformation has emerged as a pivotal factor in corporate environmental governance, attracting increasing scholarly attention, yet existing literature lacks sufficient exploration of its impact on enterprise-level carbon emission reduction. Drawing on resource-based view and transaction cost theory, the relationship between digital transformation and carbon emission reduction was examined using panel data from Chinese A-share industrial listed companies spanning 2010-2021. By applying robust econometric methods, the direct effects of digital transformation on carbon emissions were analyzed, and the mediating mechanisms and heterogeneity across different enterprise types were further investigated. Results indicate that digital transformation significantly reduces corporate carbon emissions, with production efficiency improvement and information disclosure quality serving as key mediating pathways. The emission reduction effect is more pronounced in state-owned enterprises, firms under stringent environmental regulation, and high-tech companies. Further analysis reveals that those various digital technologies—artificial intelligence, blockchain, cloud computing, and big data—all demonstrate positive environmental governance effects. The conclusions not only contribute to the literature on digital transformation from an environmental perspective but also provide valuable insights for regulators and enterprises on leveraging digital capabilities to enhance environmental governance performance.
Keywords: digital transformation; carbon emission reduction; environmental governance; production efficiency